Leveraging the power of peer support: The story and impact of Team Lavender - Agnes Barden (The Beryl Institute, 2022)
As the world continues to take inventory of the wake left by the COVID-19 pandemic, healthcare organizations and leaders remain steadfast on recovery. At Northwell Health, the largest health system in New York State, employee emotional wellness remains a constant priority. Team Lavender (TL) is an interdisciplinary group of professionals dedicated to supporting colleagues during times of stress and/or hardship. Emergent and proactive TL peer support responses/activations provide a moment of pause, reflection, teamwork, and peer support. Particularly during COVID-19 pandemic and subsequent variant surges, this innovative budget-neutral approach was recognized and leveraged to promote resiliency, humanism and holistic well-being. Experience Framework This article is associated with the Staff & Provider Engagement lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Staff%20%26%20Provider%20Engagement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.